2016
DOI: 10.1007/s00436-016-5088-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population genetics of large lungworms (Dictyocaulus, Nematoda) in wild deer in Hungary

Abstract: Dictyocaulus nematode worms live as parasites in the lower airways of ungulates and can cause significant disease in both wild and farmed hosts. This study represents the first population genetic analysis of large lungworms in wildlife. Specifically, we quantify genetic variation in Dictyocaulus lungworms from wild deer (red deer, fallow deer and roe deer) in Hungary, based on mitochondrial cytochrome c oxidase subunit 1 (cox1) sequence data, using population genetic and phylogenetic analyses. The studied Dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…T. axei seems to be a real generalist as has been shown by transmission experiments (see above), and this is corroborated by its genetic population structure with high diversity and high gene flow between sympatric hosts ( 49 ). In lungworms of the genus Dictyocaulus from wild ungulates from Hungary different gene flow rates suggested different host range capacities in the three species Dictyocaulus eckerti, Dictyocaulus capreolus , and Dictyocaulus viviparus with D. eckerti being the most generalist species, while D. capreolus seems to have a cryptic genetic structure ( 50 ). As red deer was shown to harbor lungworms, which were genetically distinct from the other Dictyocaulus species, a new name, Dictyocaulus cervi , was proposed recently ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…T. axei seems to be a real generalist as has been shown by transmission experiments (see above), and this is corroborated by its genetic population structure with high diversity and high gene flow between sympatric hosts ( 49 ). In lungworms of the genus Dictyocaulus from wild ungulates from Hungary different gene flow rates suggested different host range capacities in the three species Dictyocaulus eckerti, Dictyocaulus capreolus , and Dictyocaulus viviparus with D. eckerti being the most generalist species, while D. capreolus seems to have a cryptic genetic structure ( 50 ). As red deer was shown to harbor lungworms, which were genetically distinct from the other Dictyocaulus species, a new name, Dictyocaulus cervi , was proposed recently ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Dama spp.). Analysis of mitochondrial sequence data found weak genetic structuring in D. eckerti [ 86 ], while D. capreolus (specific to roe deer, Capreolus capreolus ), had comparatively lower genetic diversity and more strongly genetically structured populations when sampled sympatrically [ 86 ]. Dictyocaulus capreolus is susceptible to population bottlenecks if roe deer numbers fall, whereas D. eckerti can weather a crash in the population of any one host species by persisting in other host species, and thereby maintain a high census size (N, see Table 1 ).…”
Section: Parasitic Nematodes Of Wild Terrestrial Vertebratesmentioning
confidence: 99%
“…Nematode species that use more than one host species often have less structured populations than the movement of any one host species would predict. This has been observed in Trichinella spp., which shows gene flow at the continental scale [ 38 ], in Dictyocaulus eckerti , a generalist parasite of deer [ 86 ], and in Neoheligmonella granjoni [ 72 , 73 ]. The use of multiple mobile host species allows nematodes to traverse or colonise a wider range of habitats than would be possible using only a single host, and this tends to promote parasite gene flow.…”
Section: Synthesis and Outstanding Research Questionsmentioning
confidence: 99%
“…Furthermore, mtDNA is a useful and reliable marker for the identification of cryptic nematode species (Blouin, 2002). A recent study showed that mt cox 1 sequences can provide a rich source of genetic markers to assess the genetic diversity and cryptic species of Dictyocaulus lungworms (Ács et al ., 2016). Trichuris infecting primates represents a complex of cryptic species, with some species being able to infect both humans and non-human primates based on mt genome datasets (Hawash et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%